Growth, Feed, and Food Habits of Saurida tumbil (Bloch, 1795) in Jizan fisheries, Saudi Arabia - Hartono, Sugeng; Abualreesh, Muyassar; Gabr, Mohamed (Journal of King Abdulaziz University: Marine Sciences, 2024)
The current study provides the latest scientific evaluation on growth and feeding habits of Saurida tumbil in Jizan fisheries. Monthly samples were collected from September 2021 to April 2022, with a total of 343 individuals. Fish scales were used for age determination and back-calculation of fish lengths at ages to estimate growth rates and von Bertalanffy growth parameters. Several food and feeding analyses were estimated to describe the feeding habits of this species. Results showed that Saurida tumbil is categorized as carnivorous fish. Terapon (Terapon sp.) and anchovy (Encrasicholina sp.) were observed mostly in the stomach followed by sardinella (Sardinella sp.), squid (Loliginidae), and berber ponyfish (Leiognathus berbis). Vacuity index () analysis showed that Saurida tumbil is categorised as middle alimentative regularly regarding the feeding habit according to stomach fullness. The value of GaSI was 3.08 in average. The total Length – gutted weight relationship results showed that Saurida tumbil is isometric in dimensional growth and can be described based on the power function: Wgutted = 0.0067 TL3.014. The average back-calculated lengths at age were 18.5, 27.0, 32.4 and 37.4 cm corresponding to the first, second, third and fourth year of life, respectively. The von Bertalanffy growth parameters were found to be: the asymptotic length Lꝏ = 50.38 cm, growth constant K= 0.30 per year. The hypothetical age at zero length t0 = -0.48 year. The growth in length performance index (Ф') was 2.88.